Sepsis-Induced Changes in Spectral Segregation and Kinetics of Hippocampal Oscillatory States in Rats - Kala, Annu; Leemburg, Susan; Jezek, Karel (eNeuro, 2023)
Sepsis-associated encephalopathy (SAE) is a frequent severe complication of sepsis and the systemic inflammatory response syndrome, associated with high mortality and long-term neurologic consequences in surviving patients. One of the main clinical signs of SAE are discontinuous sleep periods that are fragmented by frequent awakenings. Although this brain state fragmentation strongly impacts the functionality of the nervous and other systems, its underlying network mechanisms are still poorly understood. In this work, we therefore aim to characterize the properties and dynamics of brain oscillatory states in response to SAE in an acute rat model of sepsis induced by high-dose lipopolysaccharide (LPS; 10 mg/kg). To focus on intrinsically generated brain state dynamics, we used a urethane model that spares oscillatory activity in rapid eye movement (REM)-like and nonrapid eye movement (NREM)-like sleep states. Intraperitoneal LPS injection led to a robust instability of both oscillatory states resulting in several folds more state transitions. We identified opposing shifts in low-frequency oscillations (1-9 Hz) in REM and NREM-like states under influence of LPS. This resulted in increased similarity between both states. Moreover, the state-space jitter in both states increased as well, pointing to higher within-state instability. The reduction of interstate spectral distances in 2-D state space, combined with increased within-state jitter might represent a key factor in changing the energy landscape of brain oscillatory state attractors, and hence lead to altered sleep architecture. Their emergence during sepsis might point to a mechanism underlying severe sleep fragmentation as described both in sepsis patients and SAE animal models.
Keywords: kinetika; Animals; sleep; hipokampus; Kinetics; lipopolysacharidy; Sleep, REM; activity states; sepse; Sepsis; Lipopolysaccharides; sepsis; oscillations; hippocampus; krysa rodu Rattus; spánek REM; inflammation; Hippocampus; zvířata; elektroencefalografie; Rats; Electroencephalography